Sustainability in Sport-Related Studies: A Non-Systematic Review to Increase the Sports Contribution to the 2030 Agenda - Annesi Nora; Battaglia Massimo; Frey Marco (Sciendo, 2023)
This paper aims to identify all of the unexploited potentialities of sports activities with regard to sustainability by answering the following question: Considering the priorities that the 2030 Agenda identified with regard to sustainability, what does sport contribute to the process of transition towards a more sustainable global scenario? According to the European Union Council, sport and physical activity play a strategic role in the global challenge toward sustainability and achieving the 17 SDGs. The contribution of sport to the 2030 Agenda is indeed strategic. However, through a non-systematic review, the authors have observed almost a complete absence of SDGs within sports literature. Discussing the results through the lens of the SDGs, the authors have identified a series of qualitative and quantitative research opportunities connected with the 17 SDGs and related targets. The authors have also identified a total of 27 research hypotheses. This evidence could support academics, sports managers, professionals, and practitioners in identifying their contribution to the global priorities towards sustainability.